All-India Report on Evaluation of NREGA: A Survey of Twenty Districts - Planning Commission (Planning Commission, 2009)
National Rural Employment Guarantee Scheme (NREGS) under the NREG Act is the flagship programme of Government of India which is the first of its kind The NREG Act guarantees every rural household up to 100 days of wage employment in a year within a period of 15 days of demand for such employment. Among the other things, such as creation of sustainable assets, rural infrastructure, etc., the scheme ensures better quality of life and enhanced income for rural households by providing 100 days of employment in a staggered manner, which is intended to be utilised by the beneficiaries in a rational and judicious way to combat drought, distress migration and lean agricultural season, etc. Assessment of effectiveness of the scheme vis-a-vis achievement of the desired goals and objectives depends on (a) gauging the outcome of the scheme, and (b) analysing the extent of implementation of the guidelines enshrined in the NREG Act. in letter and spirit.
Prepared with Financial Support and Research Inputs From Programme Evaluation Organisation (PEO), Planning Commission by Institute of Applied Manpower Research